Predicting the structure and stability of titanium oxide electrides. (December 2018) - Zhong, Xin; Xu, Meiling; Yang, Lili; Qu, Xin; Yang, Lihua; Zhang, Miao; Liu, Hanyu; Ma, Yanming
Abstract The search for new inorganic electrides has attracted significant attention due to their potential applications in transparent conductors, battery electrodes, electron emitters, as well as catalysts for chemical synthesis. However, only a few inorganic electrides have been successfully synthesized thus far, limiting the variety of electride examples. Here, we show the stabilization of inorganic electrides in the Ti-rich Ti–O system through first-principles calculations in conjunction with swarm-intelligence-based CALYPSO method for structure prediction. Besides the known Ti-rich stoichiometries of Ti2 O, Ti3 O, and Ti6 O, two hitherto unknown Ti4 O and Ti5 O stoichiometries are predicted to be thermodynamically stable at certain pressure conditions. We found that these Ti-rich Ti–O compounds are primarily zero-dimensional electrides with excess electrons confined in the atom-sized lattice voids or between the cationic layers playing the role as anions. The underlying mechanism behind the stabilization of electrides has been rationalized in terms of the excess electrons provided by Ti atoms and their accommodation of excess electrons by multiple cavities and layered atomic packings. The present results provide a viable direction for searching for practical electrides in the technically important Ti–O system. Titanium oxide: New locations for electrons Computer simulations predict that compounds made of oxygen and titanium atoms form cages that can host electrons in their interstices. A team led by Hanyu Liu and Yanming Ma from Jilin University, China, have investigated the possibility for materials belonging to the family of titanium dioxide, a pigment used in paints and sunscreens, to behave as electrides, materials in which electrons resemble larger negatively charged atoms in the way in which they localize and interact with the surrounding atomic structure. Their calculations show that this occurs if the amount of titanium atoms in the material exceeds that of oxygen atoms by at least a factor of 2, which allows the formation of larger cages in which electrons can be confined. The synthesis of these materials will allow to assess their significance for catalysis or other applications.